Sports anglicisms - Språkbanken Text (University of Gothenburg, 2025)
English loan-words in the Swedish sports press

Engelska lånord i svenska sportspalter
Sportanglicismer
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik